The Effect of Lined Circular Planting Methods of Sweet Corn (Zea mays Saccharata) on Diversity and Density of Weed Species - Lutfy Ditya Cahyanti; Use Etica (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2020)
The objective of the research to determine the effect of row circle method on population and diversity of weed in sweet corn. This research was conducted in the Sub District of Siman, District of Siman, Ponorogo The research used a randomized block design (CBD) with 4 kinds of planting spaces included J1 = 8 plant/(60x80) cm2, J2 = 16 plant/(60x80) cm2, J3 = 12 plant/(60x80) cm2, J4 = 1 plant/(60x 80) cm2, J5 = 1 plant/ (60x80) cm2 with mowing. Each experimental unit was repeated 5 times so that there were 25 units. The observation was done on the Summed Dominance Ratio (SDR) of weeds on 21,28, 35 and 42 DAP (day after planting). Largest SDR was found in Cynodon dactylon (54,23%) followed by broadleaf grass group (Phyllanthus nirurii, 40,5%), and Sphenoclea zeylanica (34,2%). Various planting system influenced weed species diversity. The number of weed species in 1 plant/(60x80) cm2 treatment was six species and higher than 8 plant/(60x80) cm2, 16 plant/(60x80) cm2, 12 plant/(60x80) cm2 and 1 plant/(60x80) cm2 with mowing treatment which has three species.